2013
DOI: 10.1139/cjc-2013-0132
|View full text |Cite
|
Sign up to set email alerts
|

Probing the utility of palladium complexes supported by morpholine-functionalized N-heterocyclic carbene ligands in Buchwald–Hartwig amination

Abstract: Convenient and high-yielding syntheses of two new morpholine-substituted N-heterocyclic carbene ligands, 1-Ar-3-{2-(4-morpholinyl)phenyl}imidazolidin-2-ylidene (Ar = Dipp, Mes), are described. An investigation of corresponding palladium complexes reveals hemilability, and examples of both monodentate and bidentate coordination are observed. A preliminary investigation of the activity of these palladium complexes for Buchwald–Hartwig amination catalysis is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…As an extension of our previous work on morpholine-functionalized NHC ligands, we have chosen to pursue a directly analogous ligand design in which an o -phenylene group rigidly links the phosphine and NHC donors. A series of NHC–phosphine ligands of this type have been prepared previously by Zhou and co-workers .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As an extension of our previous work on morpholine-functionalized NHC ligands, we have chosen to pursue a directly analogous ligand design in which an o -phenylene group rigidly links the phosphine and NHC donors. A series of NHC–phosphine ligands of this type have been prepared previously by Zhou and co-workers .…”
Section: Resultsmentioning
confidence: 99%
“…However, the reported synthetic route is low-yielding and inconvenient and is limited to diphenylphosphino derivatives. We therefore sought to develop a more convenient and flexible synthetic route similar to what we developed previously for the synthesis of morpholino-functionalized NHC ligands . Such morpholine-functionalized NHC ligands are prepared from o -bromoiodobenzene, whereby the ligand is generated through two palladium-catalyzed C–N cross-coupling steps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based upon the earlier research employing morpholinyl aminophenolate metal complexes, we pondered whether species containing such a structural motif could be considered a privileged class of ligand for polymerization of polar monomers including ε-CL and epoxides. Furthermore, Stradiotto and co-workers have found that morpholinyl-containing phosphines provide exceptionally stable and active catalyst systems for cross-coupling and other important reactions in organic synthesis, giving further credence to the privileged role that morpholine can play in stabilizing catalytic intermediates. In this paper, we report the synthesis and characterization of a family of cationic aluminum complexes with various counterions and their application as initiators for well-controlled ROP of ε-CL.…”
Section: Introductionmentioning
confidence: 99%